WISATA BUDAYA BERBASIS EKONOMI KREATIF MELALUI SUSTAINABLE TOURISM DI KAMPUNG BATIK OKRA SURABAYA: Creative Economy Based Culture Tour Through Sustainable Tourism In Okra Batik Village, Surabaya - Ratih Mukti Azhar; Daisy Marthina Rosyanti; Ayundha Evanthi; Ilham Hardi; Shabrina Aulia Az Zahra (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Kampung Batik Okra Surabaya is one of the new tourist destinations in Surabaya. As a new tourism product, the people of Kampung Batik Okra still need assistance in developing Kampung Batik Okra as a tourist destination for the city of Surabaya in terms of the image or brand of Kampung Batik Okra as a tourism product in the city of Surabaya and its promotion. Seeing this opportunity, Team from UPN Veterans East Java seeks to provide knowledge transfer in the form of how to improve the image or brand of Kampung Batik Okra through an e-branding strategy as strengthening existence and reaching a wider tourist market, using social media as a promotional event and compiling product catalogs for map production capabilities and market demand. This transfer of knowledge is a step towards realizing tourist destinations that have marketability by highlighting the uniqueness, beauty, authenticity, and value of tourist destinations in a sustainable manner through sustainable tourism. The purpose of this community service activity is to improve the image or brand of Kampung Batik Okra Surabaya to become widely known through cataloging or pamphlets, photo and videographic training and promotion and branding by using social media as a form of strengthening the existence of Kampung Batik Okra through e-branding. The results of this community service apart from transferring knowledge are also producing pamphlets and catalogs of tourism products as a means of promotion for Kampung Batik Okra Surabaya.